[St. Miguel Febres de Cordero award] - De La Salle University, Manila (Animo Repository, 1998)
One of the highlights of the 1998 Faculty Recognition Awards was the St. Miguel Febres de Cordero Award for most outstanding research. This was the first award which recognized significant research done by a faculty in each college.